Do More Educated Leaders Raise Citizens' Education? - Luis Diaz-Serrano; Jessica Pérez (Institute for the Study of Labor (IZA), 2013)
This paper looks at the contribution of political leaders to enhance citizens' education and investigate how the educational attainment of the population is affected while a leader with higher education remains in office. For this purpose, we consider educational transitions of political leaders in office and find that the educational attainment of population increases when a more educated leader remains in office. Furthermore, we also observe that the educational attainment of the population is negatively impacted when a country transitions from an educated leader to a less educated one. This result may help to explain the previous finding that more educated political leaders favor economic growth.
Keywords: I21; I25; I28; 330; political leaders; primary education; school achievement; political institutions